2012
DOI: 10.1108/20421161211229826
|View full text |Cite
|
Sign up to set email alerts
|

Relative value‐relevance of accounting measures based on Chinese Accounting Standards and International Financial Reporting Standards

Abstract: Purpose -This study investigates the relative value relevance of accounting measures based on Chinese Accounting Standards (CAS) and International Financial Reporting Standards (IFRS) in relation to both A-and B-share markets during three distinct phases (1994-1997, 1998-2000 and 2001-2004) over which CAS were progressively harmonized with IFRS. Design/methodology/approach -Using data for 86 Chinese listed companies which issued both A-and B-shares, we employ the price model to test for the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
2
23
0
1
Order By: Relevance
“…(), Li (), Lin and Chen (), Chamisa et al . (), Rutledge et al . (), and Qu and Zhang (), attempts to explore differences in accounting information content under CAS and IFRS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(), Li (), Lin and Chen (), Chamisa et al . (), Rutledge et al . (), and Qu and Zhang (), attempts to explore differences in accounting information content under CAS and IFRS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There may be differences of impact of IFRS adoption depending on whether the economy is of developed or developing category. Niskanen et al [31 and 32] and Bartov et al [20] are some studies anchored in developed economy while Jermakowicz and Gornik-Tomaszewski, [33], ElShamy and Al-Qenae, [34], El-Shamy and Kayed, [35] and Chamisa et al [16] are some investigations in developing countries. It is therefore possible to view another four dimensions that analytical studies may focus.…”
Section: International Letters Of Social and Humanistic Sciences Vol 69mentioning
confidence: 99%
“…If the IFRS are to be truly international accounting standards, the above impacts of IFRS must be evident in countries across the globe irrespective of political, economic and cultural diversities. Chamisa et al [16] claim that there are two constituents of studies on the value relevance of IFRS depending on the economic context in which the data are obtained. That is, whether the data from developed, developing and transitional economies.…”
Section: International Letters Of Social and Humanistic Sciences Vol 69mentioning
confidence: 99%
See 1 more Smart Citation
“…Chamisa et al [28] studied using data for 86 Chinese listed companies which issued both A-and Bshares and revealed that for both the A-share and B-share markets, both Chinese Accounting Standards (CAS)-based and IFRS-based accounting information are value relevant, but IFRS-based information is more value relevant than the CAS-based information. They claim that this is the first to investigate the relative value relevance of CAS-and IFRS-based accounting measures in both the A-and B-share markets covering all the three distinct periods when CAS was progressively harmonized with IFRS.…”
mentioning
confidence: 99%